2012
DOI: 10.1161/strokeaha.111.647065
|View full text |Cite
|
Sign up to set email alerts
|

Distributional Impact of Brain Microbleeds on Global Cognitive Function in Adults Without Neurological Disorder

Abstract: Background and Purpose-Brain microbleeds (MBs) are considered to be associated with cognitive decline and can be pathologically and topographically classified as cerebral amyloid angiopathy-related (located in lobar regions) and hypertensive microangiopathy-related (located in deep regions). We examined whether different effects on global cognitive function might be seen with different distributions of MBs. Methods-A total of 1279 adults without neurological disorders were studied prospectively. Subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 31 publications
(35 reference statements)
6
49
1
Order By: Relevance
“…[22][23][24]29,30 Some studies report that deep CMBs, 22,23 particularly those in the BG, are associated with cognitive decline, whereas others 29,30 report that lobar CMBs are associated with deficits in cognitive performance, which is in line with our results. Differences in population-based cohorts may explain why deep or lobar locations of MBs appear more prominently in different studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[22][23][24]29,30 Some studies report that deep CMBs, 22,23 particularly those in the BG, are associated with cognitive decline, whereas others 29,30 report that lobar CMBs are associated with deficits in cognitive performance, which is in line with our results. Differences in population-based cohorts may explain why deep or lobar locations of MBs appear more prominently in different studies.…”
Section: Discussionsupporting
confidence: 90%
“…23,41,42 The present study evaluated whether CMBs and their locations were associated with a variety of cognitive domains. In addition, we used susceptibility weighted imaging on a 3T MRI, which is a tool with better resolution and higher sensitivity, 8 to detect CMBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lobar microbleeds have found to be more common in patients with dementia than controls, [101][102][103][104] their causal relationship with cognition seems relatively weak. Several population-based and memory clinic studies found no association between the presence or number of lobar microbleeds and cognitive performance 78,102,[104][105][106][107] or global cognitive decline. 108,109 Positive associations between microbleeds and worse cognition are mainly found in individuals with a high MB count (>5 or >7) 110,111 or individuals diagnosed with symptomatic SVD.…”
Section: Lobar Microbleeds and Cognitionmentioning
confidence: 99%
“…CMBs have also been observed in elderly patients without known underlying pathology [13,14], as well as in other degenerative central nervous system conditions, including cerebral amyloid angiopathy (CAA) associated with Alzheimer's disease and vascular cognitive impairment [11], where they have been linked to cognitive dysfunction [15][16][17][18]. Thus, quantification of CMB characteristics may serve as a valuable metric for radiation-induced vasculopathy and resultant cognitive decline.…”
Section: Introductionmentioning
confidence: 99%